(untitled) (Research, Society and Development, 2021)
Objective: Report the experience of professional master degree students during the discipline Health Education in the Amazon, thus showing the qualification of teaching training for health professionals. Method: This report is based on the experience of 16 students from the Postgraduate Professional Master’s Degree Course in Health Education in the Amazon of the State University of Pará (UEPA) during the discipline in Health Education in the Amazon. The topics covered in the classes were: Skills and knowledge of teachers from higher education in health, DCN and innovative curricula in health, learning theories, teaching methods, educational technologies and learning assessment. Experience report: Students experienced active methodologies in practice while learning the content of the discipline. The activities proposed by the teachers were: concept map, Problem Based Learning (PBL), Simulated Jury and Team Based Learning (TBL). These strategies allowed an excellent and motivating class, as the absorption of the content became easier, pleasant, dynamic and interactive. Final considerations: The subject Health Education in the Amazon provided the students with knowledge, new strategies and practices to train and improve their performance in the classroom as a teacher, building an environment that facilitates the student’s teaching-learning process.